(untitled) (Biological Sciences - PJSIR, 2025)
Honey is natural biological sweet drug formed from the combination of plant pollen, nectar and the secretion of honey bees’ body. In the present study eleven samples of honey (Robinia pseudoacacia, Eriobotrya japonica, Justacia adhatoda, Zizyphus jujuba, Calathea allouia, Punica granatum, Otostegia limbata, Accasia modesta, Thymus seralis, Citrus sinensis and Trifolium resupinatum) from different plant sources were collected from Khyber Pakhtunkhwa, Pakistan. The honey samples were tested for physical and chemical parameter including hydroxy methyl furfuryl (HMF) test, pH, moisture content, acidity, electrical conductivity and pollen analysis. Various ranges including pH (3.43-6.00), moisture content (1.89-3.73%), EC (0.36-2.91 µSicm) and acidity (0.345-2.42 meqiKg) has been recorded. HMF result was tested for adulteration and the purest honey recorded was Eriobotrya japonica, Justacia adhatoda, Trifolium resupinatum. Samples of honey contained pollen from seventeen different species, most of which belonging to the Fabaceae family and included unifloral and polyfolral honey. Honey samples tested for antibacterial potential against Staphylococcus aureus, Escherichia coli, Salmonella typhi and Pseudomonas aeroginosa showed significant potential against P. granatum and E.coli. Antifungal potency of honey against different fungal strains Aspergillus niger, Aspergillus terreus, Fusarium oxysporum and Alternaria alternate showed that the multifolral honey was highly effective against the afore mentioned fungal species. The honey obtained from Accasia modesta shown high effectiveness against the fungus F. oxysporum. In conclusion, the physio-chemical characteristics and pharmacognostic advantages of honey derived from various plant sources showed varied features. More recommendations citing the physio-chemical and antibacterial properties of various honeys for health advantages.